Relationship Between Wedding With Mom Stress Level In Caring For Children In Prunggahan Village, Semanding Subdistrict, Tuban District - triyunita fitria damayanti (Jurnal Penelitian, 2020)
Now a days that many new mother who has a child first time experiencing stress resulting, it caused by caring the new baby born and she in not ready psycological. The problem in child care is one cause of stress in terms of social and psychological. The purpose of this reseach is to know the relation between marriage age and mother stress level in taking care a child in Prunggahan Kulon village.          The reseach method is  Corelasional Analiticby using Cross Sectional time. The population in the reseach are 66 women in Prunggahan Kulon village which suitable in inklusi criteria. The reseach sample is 57 responden which determinate by using Cluster Sampling tehnique. The variable independent is marriage age meanwhile the dependent variable is mother stress level in taking care a child. The instrument in collecty the data is quetioner. The reseach analysis is using Contingency Coefficient C.          The statistic result shows the variable marriage age is significant with mother stress level in taking care a child is ρ-value (0,000). The result of this reseach hope can be valuable in teaching process and enlarge the society knowladge in taking care a chil.